Durability and thermal properties of cement mortar containing Algerian bentonite - Hadja Kawthar; Bouksani Omar; Khelifa Kerfah Ilyas; Benhadji Maissen; Kharchi Fattoum; Abba Fatiha (International Journal of Computational and Experimental Science and Engineering, 2025)
Cement industry generates a serious problem for the environment. Its production, through the calcination of limestone rocks and the energy used, releases a significant amount of carbon dioxide, contributing to the greenhouse effect. Finding solutions to reduce the quantity of cement necessary for the manufacture of mortar can minimize energy consumption, reduce pollution and thus preserve the environment. The aim of this experimental work was to partially replace the cement with bentonite in mortars at varying percentages of 0%, 5%, 10%, 15%, 20%, 25%, and 30%. The effects of bentonite on mechanical strengths, such as compressive and flexural strengths, as well as on thermal performance by assessing the thermal conductivity coefficient were investigated. The experimental results showed that the partial replacement of cement with bentonite significantly improved the thermal insulation of mortars, since the thermal conductivity decreased from 1.59 to 1.29w/mK. However, the mechanical strengths decreased slightly as the bentonite content increased until 15% replacement. Beyond 15% replacement of cement with bentonite, the compressive and flexural strengths decrease abruptly. Finally, the durability of the mortar with bentonite is critical since water absorption increases.